ChemInform Abstract: Methods and Various Catalysts Used for Chalcone Synthesis. Issue 33 (25th July 2013) - Bukhari, Syed Nasir Abbas; Jasamai, Malina; Jantan, Ibrahim; Ahmad, Waqas
Abstract Review: 83 refs.